An Assessment of the State of Misinformation Regarding Eye Diseases and Their Treatment in the General Public - Saba Alkhairy; Farnaz Siddiqui; Muhammad Nizamuddin; Ramiz Kirmani; Muhammad Sohaib; Mahad Mirza Baig (Liaquat National Journal of Primary Care, 2023)
Background: The importance of eye health in the overall well-being of an individual continues to be a neglected topic. As a result, potentially harmful knowledge gaps prevail. Myths and misconceptions continue to spread in low and middle-income regions such as Karachi. Objective: To identify perceptions of eye diseases and their treatment in a local subset of the population as well as the extent of their knowledge of ophthalmological conditions based on their education level. Methodology: This is a cross-sectional study conducted in the Out-Patient Department of Ophthalmology (OPD) of Dow International Medical College (DIMC), Karachi, from January 2021 until August 2021. Informed consent was signed, and each subject was interviewed using a questionnaire regarding their understanding of eye diseases. The data collected was then entered into the pro forma which was analyzed using SPSS version 23. Results: A total of 390 subjects were selected from the OPD. Their age ranged from 18 to 79 years with a mean age of 36.4 ± 14.2 years. The participants of the study consisted of 182 (46.7%) males and 208 (53.3%) females. However, There was a general perspective that cataract is a condition that can be corrected by using eye drops (18.7%) and that fennel, almonds, and rock candy are beneficial for the eyes (63.3%). Among people of all educational standards, the highly educated significantly demonstrated correct knowledge regarding whether the use of Surma and kajal (p=0.030), and Arq-e-Gulab (p=0.002) are beneficial and the need for a soft diet after cataract surgery (p=0.030). Conclusion: Despite the cultural beliefs we observed, people generally exhibited a relatively reasonable level of knowledge in terms of safe eye care practice